2022
DOI: 10.1155/2022/6300329
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutations and Telomerase in Melanoma

Abstract: Malignant melanoma is an extremely malignant tumor with a high mortality rate and an increasing incidence with a high mutation load. The frequency of mutations in the TERT promoter exceeds the frequency of any known noncoding mutations in melanoma. A growing number of recent studies suggest that the most common mutations in the TERT promoter (ATG start site −124C>T and −146C>T) are associated with increased TERT mRNA expression, telomerase activity, telomere length, and poor prognosis. Recently, it has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Retained H3 K27 trimethylation has been reported in MPNSTs occurring in a spinal location. 33 Although TERT promoter mutations are commonly seen in IDH wild-type GBMs, they can also be encountered in many other neoplasms, including meningioma, 34 pleomorphic xanthoastrocytoma, 35 oligodendroglioma IDH-mutant and 1p/19q-codeleted, 36 melanoma, 37 and rare examples of MPNST. 38 Thus, the identification of a TERT promoter mutation alone is not diagnostic of GBM without accompanying evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Retained H3 K27 trimethylation has been reported in MPNSTs occurring in a spinal location. 33 Although TERT promoter mutations are commonly seen in IDH wild-type GBMs, they can also be encountered in many other neoplasms, including meningioma, 34 pleomorphic xanthoastrocytoma, 35 oligodendroglioma IDH-mutant and 1p/19q-codeleted, 36 melanoma, 37 and rare examples of MPNST. 38 Thus, the identification of a TERT promoter mutation alone is not diagnostic of GBM without accompanying evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The TERT-promoter mutations upregulate telomerase activity, allowing cancer cells to survive, and prior studies have shown TERT-mutant melanomas to have earlier recurrence and progression, as well as resistance to treatment. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Alteration in the TERT gene includes genomic gains/amplifications, promoter rearrangements, and "hotspot" promoter mutations at a position relative to the transcription start site [39]. These alterations have been reported in multiple cancer types, especially TERT promoter mutations, which are associated with increased TERT expression [20,21,[40][41][42]. In a pan-cancer study of somatic TERT promoter mutations and amplification, Sounak et al found that among 30,733 specimens, almost 11.3% of cases with TERT promoter mutation were accompanied by 2.3% TERT amplification and 86.3% with no TERT amplification or promoter mutation [40].…”
Section: Effects On Tert In Cancer Formation Transcriptional Regulationmentioning
confidence: 99%